Clinical characteristics, treatment patterns, and persistence in individuals with type 2 diabetes initiating a glucagon-like peptide-1 receptor agonist: A retrospective analysis of the Diabetes Prospective Follow-Up Registry - Jung, Heike; Tittel, Sascha R.; Schloot, Nanette C.; Heitmann, Elke; Otto, Thorsten; Lebrec, Jeremie; Pavel, Marianne Ellen; Lanzinger, Stefanie (Diabetes Obesity & Metabolism, 2023)
Aims: To describe clinical characteristics, treatment patterns and glucagon-like peptide-1 receptor agonist (GLP-1 RA) persistence in individuals with type 2 diabetes (T2D) initiating their first GLP-1 RA. Materials and Methods: A real-world analysis of adults with T2D initiating GLP-1 RA therapy between 2007 and June 2020 from the multicentre Diabetes Prospective Follow-Up (DPV) Registry, stratified by antidiabetes therapy at the time of GLP-1 RA initiation: oral antidiabetic drugs (OAD), insulin ± OAD or lifestyle modification (LM). GLP-1 RA treatment persistence in individuals with ≥12 months follow-up was determined by Kaplan-Meier analysis. Results: Overall, 15 111 individuals with T2D initiating GLP-1 RA therapy (55% men) were identified; median [interquartile range (IQR)] age [58.7 (50.6-66.7) years], diabetes duration [8.5 (3.6-14.7) years], glycated haemoglobin [HbA1c; 8.2 (7.1-9.8)%]. Median (95% confidence interval) GLP-1 RA persistence in eligible individuals (n = 5189) was 11 (10-12) months; OAD 12 (11-14) months (n = 2453); insulin ± OAD 11 (9-12) months (n = 2204); and LM 7 (5-9) months (n = 532). Median treatment persistence tended to increase from 2007-2012 to 2017-2020. Median (IQR) HbA1c decreased from baseline [8.2 (7.1-9.8)%] to discontinuation [7.5 (6.6-8.7)%], with a greater decrease observed in individuals with persistence >12 months versus ≤12 months. Individuals who discontinued GLP-1 RA therapy predominantly switched to insulin (if not already using) or dipeptidyl peptidase-4 inhibitors. Conclusion: Real-world registry data revealed improved outcomes with longer median GLP-1 RA persistence; 50% of patients overall achieved HbA1c <7% at 12 months. Persistence was highest with baseline OAD and/or insulin, and tended to increase over the period 2007-2020.
CRIS-Team Scopus Importer:2023-04-07
Keywords: database research; GLP-1 analogue; incretin therapy; type 2 diabetes